Enantio- and diastereocontrolled total synthesis of (+)-strictifolione - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Naidu, S. Vasudeva; Dhavale, Dilip D. (European Journal of Organic Chemistry, 2010)
A concise and practical enantioselective synthesis of (+)-strictifolione has been achieved in high diastereomeric excess using Jacobsen's hydrolytic kinetic resolution, proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of aldehyde and cross olefin/ring-closing metathesis as the key steps.
Keywords: Asymmetric synthesis; Hydrolytic kinetic resolution; lactones; Natural products; organocatalysis; Ring-closing metathesis; Total synthesis

Enantioselective synthesis of (+)-alpha-conhydrine and (-)-sedamine by L-proline-catalysed alpha-aminooxylation - Shaikh, Tanveer Mahamadali; Sudalai, Arumugam (European Journal of Organic Chemistry, 2010)
An efficient organocatalytic approach to the enantioslective synthesis of two important piperidine alkaloids, namely (+)-alpha-conhydrine (98% ee) and (-)-sedamine (95% ee), by L-proline-catalysed alpha-aminooxylation of aldehydes has been developed. The strategy involves an intramolecular cyclization to construct the piperidine core.
Keywords: alkaloids; Amino acids; Aminooxylation; Enantioselectivity; organocatalysis

Organocatalytic route to the synthesis of lactone moiety of compactin and mevinolin - Kumar, Pradeep; Pandey, Menaka; Gupta, Priti; Dhavale, Dilip D. (Tetrahedron Letters, 2010)
An efficient synthesis of lactone moiety of compactin has been achieved. The stereogenic centers were generated by means of iterative proline-catalyzed sequential alpha-aminoxylation and Horner-Wadsworth-Emmons (HWE) olefination of aldehydes. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Aminoxylation; Compactin; Lactone; organocatalysis; Proline

Synthesis of (R)-coniine and (S)-coinicine via organocatalytic alpha-aminoxylation of an aldehyde - Kondekar, Nagendra B.; Kumar, Pradeep (Synthesis-Stuttgart, 2010)
A short and efficient synthesis of the indolizidine alkaloid (S)-coinicine has been achieved using organocatalytic sequential alpha-aminoxylation and Horner-Wadsworth-Emmons olefination of an aldehyde catalyzed by L-proline. Similarly, a common organocatalytic alpha-aminoxylation route has been developed for the asymmetric synthesis of both (R)-coniine and (S)-coinicine.
Keywords: hemlock alkaloids; organocatalysis; Proline; sequential reactions; synthesis

N-Heterocyclic carbene catalyzed umpolung of michael acceptors for intermolecular reactions - Biju, Akkattu T.; Padmanaban, Mohan; Wurz, Nathalie E.; Glorius, Frank (Angewandte Chemie-International Edition, 2011)
eahciM! The N-heterocyclic carbene catalyzed umpolung of Michael acceptors proceeds through the formation of a deoxy-Breslow intermediate (see scheme; EWG=electron-withdrawing group). This nucleophilic species can react with other Michael acceptors in an intermolecular fashion, thereby resulting in the formation of homo- or heterodimeric olefins. This “Michael umpolung” should become a valuable method for the formation of densely functionalized olefins.
Keywords: carbenes; Michael acceptors; nitrogen heterocycles; organocatalysis; umpolung

Organocatalytic asymmetric 1,6-addition reactions - Biju, Akkattu T. (Chemcatchem, 2011)
Keywords: Asymmetric synthesis; catalysis; Michael addition; organocatalysis; phase-transfer catalysis

Comprehensive study on the effect of acid additives in 1(R),2(R)-Bis[(S)-prolinamido]cyclohexane catalyzed direct asymmetric aldol reactions in aqueous media - Bhowmick, Sudipto; Kunte, Sunita S.; Bhowmick, Kartick C. (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2015)
The catalytic efficacy of (1R,2R)-bis[(S)-prolinamido]cyclohexane 1, prepared from the readily available natural amino acid L-proline has been studied for the direct asymmetric aldol reaction of cyclohexanone with substituted benzaldehydes at room temperature in presence of various acid additives. A wide variety of acids e.g. aliphatic fatty acid, chiral acid, sulphonic acid, aromatic acid, etc. have been used as additive for the aldol reaction in aqueous media. A loading of 10 mol% of catalyst 1 is employed in this reaction, and good yields (up to 98% yield), diastereoselectivity (up to 96% de) and enantioselectivities (up to 87% ee) can be achieved in aqueous media within very short reaction time (1-4 hours).
Keywords: acid additives; aqueous media; Asymmetric synthesis; direct aldol reaction; organocatalysis

Concise enantioselective synthesis of naturally active (S)-3-hydroxypiperidine - Dey, Soumen; Karabal, Pratibha U.; Sudalai, Arumugam (Synthetic Communications, 2015)
A short and efficient enantioselective synthesis of natural product (S)-3-hydroxypiperidine has been achieved starting from commercially available raw materials employing two catalytic routes: (i) cocatalyzed hydrolytic kinetic resolution (HKR) of racemic methyl-3-(oxiran-2-yl)propanoate; (ii) proline-catalyzed -aminooxylation followed by Horner-Wardsworth-Emmons olefination in high enantiomeric purity (97% ee) and high overall yield (38%).
Keywords: Asymmetric synthesis; bioactivity; Enantioselectivity; Natural products; organocatalysis

Enantioselective synthesis of spirocyclohexadienones by NHC-catalyzed formal [3+3] annulation reaction of enals - Yetra, Santhivardhana Reddy; Mondal, Santigopal; Mukherjee, Subrata; Gonnade, Rajesh G.; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2016)
The enantioselective synthesis of pyrazolone-fused spirocyclohexadienones was demonstrated by the reaction of alpha,beta-unsaturated aldehydes with alpha-arylidene pyrazolinones under oxidative N-heterocyclic carbene (NHC) catalysis. This atom-economic and formal [3+3] annulation reaction proceeds through a vinylogous Michael addition/spiroannulation/dehydrogenation cascade to afford spirocyclic compounds with an all-carbon quaternary stereocenter in moderate to good yields and excellent ee values. Key to the success of the reaction is the cooperative NHC-catalyzed generation of chiral alpha,beta-unsaturated acyl azoliums from enals, and base-mediated tandem generation of dienolate/enolate intermediates from pyrazolinones.
Keywords: annulation reactions; asymmetric catalysis; N-heterocyclic carbenes; organocatalysis; spiro compounds

Recent advances in N-heterocyclic carbene (NHC)-catalysed benzoin reactions - Menon, Rajeev S.; Biju, Akkattu T.; Nair, Vijay (Beilstein Journal of Organic Chemistry, 2016)
N-Heterocyclic carbenes (NHCs) have emerged as a powerful class of organocatalysts that mediate a variety of organic transformations. The Benzoin reaction constitutes one of the earliest known carbon-carbon bond-forming reactions catalysed by NHCs. The rapid growth of NHC catalysis in general has resulted in the development of a variety of benzoin and benzoin-type reactions. An overview of such NHC-catalysed benzoin reactions is presented.
Keywords: acyloin reaction; benzoin reaction; N-heterocyclic carbenes; organocatalysis; umpolung

Catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V.; Khot, S. S.; Lad, U. P.; Desai, U. V.; Wadgaonkar, P. P. (Research on Chemical Intermediates, 2017)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone(A (R))-KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone-KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine-Oxone as an unprecedented catalyst-oxidant combination. [GRAPHICS] .
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides

N-Heterocyclic carbene-catalyzed aldol-lactonization of ketoacids via dynamic kinetic resolution - Mondal, Santigopal; Mukherjee, Subrata; Das, Tamal Kanti; Gonnade, Rajesh; Biju, Akkattu T. (ACS Catalysis, 2017)
N-Heteroryclic carbene (NHC)-catalyzed enantioselective aldol lactonization of acyclic ketoacids, proceeding via dynamic kinetic resolution, is presented. The carbene generated from the chiral anninoinclanol-derived triazolium salt in the presence of LiCl was the key for the success of this transformation. The reaction allowed the diastereoselective and enantioselective synthesis of cyclopentane-fused beta-lactones having three contiguous stereocenters. The reaction products are shown to undergo substrate-controlled beta-lactone opening in the presence of amines to afford succinimide derivatives with four contiguous stereocenters.
Keywords: aldol lactonization; beta-lactones; DKR strategies; ketoacids; N-heterocyclic carbenes; organocatalysis

Erratum to: catalyst-free oxidation of sulfides to sulfoxides and diethylamine catalyzed oxidation of sulfides to sulfones using oxone as an oxidant - Kupwade, R. V. (Research on Chemical Intermediates, 2018)
We describe here our journey from the failure of our attempts in controlled oxidation of sulfides to sulfoxides using an Oxone®–KBr combination to our success in the development of a catalyst-free protocol for the oxidation of sulfides to sulfoxides using Oxone as an oxidant. We also describe the failure of our attempts at the oxidation of sulfides to sulfones using an excess of Oxone–KBr as well as Oxone, and our success towards the development of a rapid, scalable and chromatography-free protocol for the oxidation of sulfides to sulfones using diethylamine–Oxone as an unprecedented catalyst–oxidant combination.
Keywords: diethylamine; organocatalysis; Oxidation; Oxone; Sulfones; Sulfoxides

Organocatalytic asymmetric cascade reaction of gamma-substituted deconjugated butenolides with o-formyl-beta-nitrostyrene - Deepake, Siddharth K.; Lanjewar, Atul B.; Thatikonda, Thanusha; Gonnade, Rajesh G.; Das, Utpal (ChemistrySelect, 2018)
An efficient chemo-, diastereo- and enantio-selective cascade synthesis of functionalized indanols bearing four contiguous stereogenic centres has been developed via the reaction of beta,gamma-butenolides with o-formyl-beta-nitrostyrenes in the presence of bi-functional hydrogen-bonding catalyst. Indanol derivatives containing gamma,gamma-disubstituted butenolides were obtained in good yields and with moderate to high enantioselectivities/diastereoselectivities.
Keywords: butenolides; Cascade reaction; Enantioselectivity; Indanol; organocatalysis

Tris-hydroxymethylaminomethane (THAM): An efficient organocatalyst in diversity-oriented and environmentally benign synthesis of spirochromenes - Khot, Supriya S.; Anbhule, Prashant V.; Desai, Uday V.; Wadgaonkar, Prakash P. (Comptes Rendus Chimie, 2018)
Tris-hydroxymethylaminomethane has been demonstrated to be an efficient organocatalyst in diversity-oriented synthesis of medicinally prevalent spirochromenes by one-pot, three-component reactions between isatins, malononitrile, and enolizable CH acids like dimedone, 4-hydroxycoumarin, 4-hydroxy-N-methylquinolin-2-one, or in situ generated 2-methylpyrazolon-2-one. Biodegradability and extremely low cost of the catalyst are the noteworthy features of this chromatography-free protocol.
Keywords: green chemistry; Multicomponent synthesis; organocatalysis; Spirochromenes; Tris-hydroxymethylaminomethane

Concise formal synthesis of (-)-(6R,11R,14R)-colletallol via D-proline catalysed alpha-aminooxylation-Wittig olefination strategy - Dey, Soumen; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient enantioselective formal synthesis of marine macrolide (-)-(6R,11R,14R)-colletallol has been achieved starting from commercially available raw materials. The key reactions include the D-proline catalyzed a-aminooxylation of aldehyde followed by Horner-Wardsworth-Emmons olefination in a sequential fashion to give the macrolide key intermediate 5 in high enantiomeric purity (97% ee) and high overall yield (32%).
Keywords: alpha-aminoxylation; Asymmetric synthesis; Enantioselectivity; Natural products; organocatalysis

N-Heterocyclic carbene-catalyzed umpolung of imines for the enantioselective synthesis of dihydroquinoxalines - Das, Tamal Kanti; Ghosh, Avik; Balanna, Kuruva; Behera, Pradipta; Gonnade, Rajesh G.; Marelli, Udaya Kiran; Das, Abhijit Kumar; Biju, Akkattu T. (ACS Catalysis, 2019)
N-heterocyclic carbene (NHC) organocatalysis is widely employed for the umpolung of aldehydes and recently to the umpolung of Michael acceptors and aldimines. Described herein is the NHC-organocatalyzed umpolung of aldimines for the enantioselective synthesis of nitrogen heterocycles. The bisimines generated from the condensation of 1,2-phenylenediamines and salicylaldehydes undergo intramolecular cyclization in the presence of a chiral NHC catalyst, resulting in the formation of dihydroquinoxalines in moderate to good yields and er values. Detailed DFT studies shed light on the role of -OH groups in stabilizing the initially generated aza-Breslow intermediates via intramolecular hydrogen bonds. Preliminary photophysical studies on the synthesized dihydroquinoxalines revealed that these molecules can be used for the sensing of various acids and bases.
Keywords: dihydroquinoxalines; imines; N-heterocyclic carbenes; organocatalysis; umpolung

Proline catalyzed sequential alpha-amination/ Prins/ Ritter amidation of aldehydes: new method of construction of tetrahydropyran units - Ahuja, Brijbhushan; Gadakh, Sunita; Sudalai, Arumugam (Indian Journal of Chemistry Section B-Organic Chemistry Including Medicinal Chemistry, 2019)
An efficient ``one-pot'' synthetic method toward highly substituted tetrahydrofuran (THP) units is reported. The key transformation involves an atom-efficient sequential proline catalyzed alpha-amination of aldehydes to give alpha-aminated aldehydes in situ and the subsequent cyclomerization with homoallylic alcohols under Prins/Ritter conditions. Notably, this method provides access to enantiopure 1,2-syn and 1,4-anti diamino alcohols via reductive ring opening of THP units.
Keywords: alpha-aminoxylation; organocatalysis; Proline catalyzed; sequential; tetrahydropyran unit

NHC-catalyzed desymmetrization of N-aryl maleimides leading to the atroposelective synthesis of N-Aryl succinimides - Barik, Soumen; Shee, Sayan; Das, Soumik; Gonnade, Rajesh G.; Jindal, Garima; Mukherjee, Subrata; Biju, Akkattu T. (Angewandte Chemie-International Edition, 2021)
Although the construction of axially chiral C-C bonds leading to the atroposelective synthesis of biaryls and allied compounds are well-known, the related synthesis of compounds bearing axially chiral C-N bonds are relatively rare. Described herein is the N-heterocyclic carbene-catalyzed atroposelective synthesis of N-aryl succinimides having an axially chiral C-N bond via the desymmetrization of N-aryl maleimides. The NHC involved intermolecular Stetter-aldol cascade of dialdehydes with prochiral N-aryl maleimides followed by oxidation afforded N-aryl succinimides in good yields and ee values. Preliminary studies on rotation barrier for the C-N bond, the temperature dependence, and detailed DFT studies on mechanism are also provided.
Keywords: asymmetric catalysis; axial chirality; desymmetrization; N-heterocyclic carbenes; organocatalysis

N-heterocyclic carbene-catalyzed atroposelective synthesis of N-N axially chiral 3-amino quinazolinones - Balanna, Kuruva; Barik, Soumen; Barik, Shilpa; Shee, Sayan; Manoj, Niket; Gonnade, Rajesh G.; Biju, Akkattu T. (ACS Catalysis, 2023)
Although the atroposelective synthesisof biaryls and related compoundsbearing axially chiral C-C bonds is well-known, the synthesisof axially chiral C-N bond-containing compounds is relativelyless explored, and the construction of axially chiral N-N bondshas received only scant attention. Demonstrated herein is the N-heterocycliccarbene (NHC)-catalyzed selective amidation reaction, leading to theatroposelective synthesis of N-N axially chiral 3-amino quinazolinones.The NHC-catalyzed reaction of quinazolinones containing a free N-Hmoiety with & alpha;,& beta;-unsaturated aldehydes under oxidativeconditions furnished the atropisomeric quinazolinone derivatives undermild conditions and broad scope. Preliminary studies on experimentaland density functional theory-based N-N rotational barrierdetermination are also presented.
Keywords: amino quinazolinones; asymmetriccatalysis; axial chirality; N-heterocycliccarbenes; organocatalysis

Organophosphites: an addition to the arsenal of organocatalysts - Baral, Nilofar; Rani, Soniya; Saikia, Pinku; Maity, Pradip (European Journal of Organic Chemistry, 2023)
Organophosphites are nucleophilic in nature and can act as a good leaving group owing to the stability of the phosphite anion. This dual reactivity makes them good candidates for nucleophilic organocatalysis. However, phosphites were introduced only in 2004 as the umpolung catalyst for acylsilane substrates utilizing sequential Brook rearrangements. Very recently, phosphites have been reported to catalyze aza-rearrangements and radical reactions. In this review, we discuss the reactivity parameters to understand its lack of use, as well as the potential for catalysis.
Keywords: acylradical; azaacyl equivalent; cylanion; organocatalysis; phosphite

"Weak" C-H•••S interaction drives enantioselectivity in cinchona alkaloid complex catalyzed thiocyanation - Banerjee, Subhrashis; Vanka, Kumar (Chemistry-An Asian Journal, 2023)
The great success of asymmetric organocatalysis has made it one of the most important advancements made in chemistry in the past two decades. A significant achievement in this context is the asymmetric organocatalysis of the thiocyanation reaction. In the current study, computational studies with density functional theory have been done in order to understand an interesting experimental finding: the reversal of enantioselectivity from R to S when the electrophile is changed from beta-keto ester to oxindole for the thiocyanation reaction with the cinchona alkaloid complex catalyst. The calculations reveal an unusual fact - the principal reason for the reversal is the presence of the C-H center dot center dot center dot S noncovalent interaction, which is present only in the major transition states in each of the two nucleophile cases. Only recently has it been realized that the supposedly weak C-H center dot center dot center dot S noncovalent interaction has the properties of a hydrogen bond, and the fact that this interaction is the cause of enantioselectivity has relevance, because of the large number of asymmetric transformations involving the sulphur heteroatom.
Keywords: Density functional calculations; Enantioselectivity; noncovalent interactions; organocatalysis; reaction mechanisms

Heterogeneous acid-base organocatalyst for cascade deacetalisation-knoevenagel condensations - Chhetri, Ashis; Maibam, Ashakiran; Maniam, Subashani; BabaRao, Ravichandar; Wilson, Karen; Lee, Adam F.; Mitra, Joyee (ChemSusChem, 2024)
Multifunctional heterogeneous catalysts are an effective strategy to drive chemical cascades, with attendant time, resource and cost efficiencies by eliminating unit operations arising in normal multistep processes. Despite advances in the design of such catalysts, the fabrication of proximate, chemically antagonistic active sites remains a challenge for inorganic materials science. Hydrogen-bonded organocatalysts offer new opportunities for the molecular level design of multifunctional structures capable of stabilising antagonistic active sites. We report the catalytic application of a charge-assisted, hydrogen-bonded crystalline material, bis(melaminium)adipate (BMA), synthesised from melamine and adipic acid, which possesses proximate acid-base sites. BMA exhibits high activity for the cascade deacetalisation-Knoevenagel condensation of dimethyl acetals to form benzylidenemalononitriles under mild conditions in water; BMA is amenable to large-scale manufacture and recycling with minimal deactivation. Computational modelling of the melaminium cation in protonated BMA explains the observed catalytic reactivity, and identifies the first demethoxylation step as rate-limiting, which is in good agreement with time-dependent 1H NMR and kinetic experiments. A broad substrate scope for the cascade transformation of aromatic dimethyl acetals is demonstrated.
Keywords: Antagonistic acid-base sites; Charge-assisted hydrogen bonding; Chemical cascade; organocatalysis; Sustainable catalysis

Pushing the boundaries of pnictogen-bonding organocatalysis: a clash of Sb(III) versus Bi(III) - Sharma, Jyoti; Dash, Soumya Ranjan; Vanka, Kumar (ChemPhysChem, 2025)
The sigma-hole-mediated noncovalent organocatalysis involving the pnictogen (Pn) elements has thus far been explored mostly from nitrogen to antimony, with antimony identified as the most effective catalyst. Herein, density functional theory calculations have been carried out to demonstrate that tri-aryl (Ar)-substituted bismuth(III) complexes can outperform their antimony counterparts in both anion (Cl-) binding and catalytic activity. Using a range of computational methods, a good correlation between the sigma-hole strength, chloride binding affinity, and the reaction barrier is established. Notably, the findings reveal that dispersion interactions are the dominant force in catalysts with weaker sigma-holes, while electrostatic interactions prevail in catalysts with stronger sigma-holes (for the anion abstraction step). In all cases, Bi(III) catalysts emerge as the winner over the Sb(III) analogues. Additionally, beyond the primary Pn. . .Cl interactions, several secondary interactions such as Cl. . .H/F-C(Ar) and Cl-. . . H-C(Si-TBS) also play a significant role in stabilizing the transition states.
Keywords: Antimony; Bismuth; organocatalysis; pnictogen; sigma (sigma) holes

Sequential nitro-michael addition and reductive cyclization cascade reaction for diastereoselective synthesis of multifunctionalized 3,3′-pyrrolidinyl-spirooxindoles - Nichinde, Chandrakant B.; Bhati, Meema; Girase, Amardipsing S.; Patil, Baliram R.; Chaudhari, Suryakant S.; Gamidi, Rama Krishna; Joshi, Kavita; Kinage, Anil K. (European Journal of Organic Chemistry, 2025)
In this investigation, we elucidated, one-pot two stage efficient synthesis of multifuctionalized spiro[oxindole -3,3 `-pyrrolidine]. The methodology proceeds via organocatalyzed nitro-Michael addition reaction between indolylidenecyanoesters and nitroalkanes to formed nitro-Michael adduct which transformed into multifunctionalized 3,3 `-pyrrolidinyl-spirooxindoles by metal catalyzed reductive cyclization cascade. DFT investigations were conducted to elucidate the mechanism underlying the preferential reduction of the nitro group, with subsequent attack on the nitrile and ester groups remain inert throughout the reaction process. The approach is operationally simple, easily scalable, exhibits compatibility with readily accessible starting material and catalysts, thereby emphasizing cost-effectiveness.
Keywords: 3 `-pyrrolidinyl spirooxindoles; DFT study for regioselective cyclization; Diastereoselective 3; organocatalysis; Pd/C catalysed partial reductive spirocyclization